Morphometric Discrimination of Females of Five Species of Anopheles of the Subgenus Nyssorhynchus from Southern and Northwest Colombia (2002)
ABSTRACT: The most important vectors of human Plasmodium in the neotropics belong to the subgenus Nyssorhynchus. These species are generally sympatric in terms of their geographical distributions. Some are difficult to identify based solely on examination of adult females using the available morphological keys, in these cases examination of immature stages and male genitalia is required to make correct determinations. However, in epidemiological studies it is necessary to identify the species of adult females which are found near humans, i.e. in studies of malaria transmission or evaluation of control measures. The purpose of the present study was to evaluate the discrimination of adult females of different species of Nyssorhynchus isolated mainly from Southern Colombia (department of Putumayo), using morphometric analysis. Adult females were obtained after rearing larvae collected in natural breeding places and from the progeny of females collected on humans. The morphological characteristics of the immature stages allowed the identification of four species of the subgroup Oswaldoi from Southern Colombia: Anopheles rangeli Gabaldon, Cova Garcia & Lopez, An. oswaldoi (Peryassu), An. benarrochi Gabaldon, Cova Garcia & Lopez and An. triannulatus (Neiva & Pinto). The species An. nuneztovari (Gabaldon) from the Northwest of Colombia was included for comparison. Morphometric analysis allowed differentiation of the females of all species to a confidence level approaching 90% using principal components analysis of 10 wing and leg variables, followed by canonical variate analysis of the first four principal components. We conclude that morphometrics may represent a useful taxonomic tool for this group and that its use should be further studied.